"We Were Absolutely in the Dark": Latent Analysis of Developmental Disability Nurses' Experiences During the COVID-19 Pandemic. (14th September 2021) - Desroches, Melissa L.; Fisher, Kathleen; Ailey, Sarah; Stych, Judith
People with developmental disabilities (DD) are devastatingly impacted by COVID-19, yet no studies have explored the experiences of developmental disability nurses during the pandemic. In April 2020, as part of a multiple method study, we used manifest content analysis to evaluate nurses' 287 open-ended responses to our online survey question: "What is the experience of being a developmental disability nurse while encountering challenges to meeting basic care needs during the early COVID-19 pandemic?" We identified four themes: living with fear and stress, helping others to understand and cope, navigating a changing landscape, and being left out. Findings reinforce the need for accessible health information for people with developmental disability, guidelines relevant to developmental disability nursing settings, emotional support for developmental disability nurses, and education of health care professionals about the contribution of the developmental disability nurse in supporting the holistic well-being of people with DD.